2011
DOI: 10.1002/jobm.201100228
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of environmental factors for improved production of rhamnolipid biosurfactant by Pseudomonas aeruginosa RS29 on glycerol

Abstract: A biosurfactant producing Pseudomonas aeruginosa RS29 (identified on the basis of 16S rDNA analysis) with good foaming and emulsification properties has been isolated from crude oil contaminated sites. Optimization of different environmental factors was carried out with an objective to achieve maximum production of biosurfactant. Production of biosurfactant was estimated in terms of surface tension reduction and emulsification (E24) index. It was recorded that the isolated strain produced highest biosurfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 52 publications
4
20
0
1
Order By: Relevance
“…The band at 1100 cm À1 in the spectra obtained from the rhamnolipid was due to C-O-C stretching of ether linkage. The results are in good agreement with the spectra for rhamnolipid obtained by Heyd et al [30] and Saikia et al [17]. Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The band at 1100 cm À1 in the spectra obtained from the rhamnolipid was due to C-O-C stretching of ether linkage. The results are in good agreement with the spectra for rhamnolipid obtained by Heyd et al [30] and Saikia et al [17]. Fig.…”
Section: Resultssupporting
confidence: 91%
“…Several studies have been performed on the production of biosurfactant using various organisms, such as Pseudomonas putida and Pseudomonas fluorescens [15], Pseudomonas aeruginosa [16,17], Bacillus subtilis [14,18], Pseudomonas cepacia [19], and various carbon sources like date molasses, corn liquor, cooking oil, etc., other than pure liquid and solid hydrocarbon. Though some studies have been reported on the production of biosurfactant using pure hydrocarbons [20,21]; there is a need to have better insights into comparative information on the efficacy of suitable microorganisms on the production of biosurfactant suitable for hydrocarbon degradation.…”
Section: Introductionmentioning
confidence: 99%
“…After optimizing the inocula conditions, the yield of the lipopeptide produced by Bacilus subtilis SPB1 was enhanced to 3.4 g/L [42]. Pseudomonas aeruginosa RS29 produced a rhamnolipid after 48 h of incubation at 370C and pH 7-8 and the yield obtained after optimizing the various environmental factors was 0.80 g/L [43].…”
Section: Improvement In Biosurfactant Production and Their Applicationsmentioning
confidence: 99%
“…Biosurfactants are structurally diverse group of surfaceactive substances produced by different groups of microorganisms during late log or stationary phase of the growth (Desai and Banat, 1997). Biosurfactant production is regulated by available carbon source, pH, salinity and temperature (Saikia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%